In-vitro antioxidative activity of phenolic and flavonoid contents of leaves of medicinal plant -ehretia laevis - RASIKA C. TORANE,; GAYATRI S. KAMBLE,; SUJATA V.UPADHYE,; NIRMALA R. DESHPANDE, (International Journal of Pharma and Bio Sciences, 2011)
The aim of this work was to estimate the total phenolic and flavonoid content and to evaluate in vitro antioxidant activity of methanolic extract of Ehretia laevis. The methanol extract (A) of leaves of E.laevis was analysed for the total phenolic and flavonoid contents and antioxidant activity. The content of total phenolics in the extract was determined spectrometrically according to the Folin-Ciocalteu procedure and calculated as catechol equivalent. The content of total flavonoids in the extract was determined and calculated as quercetin equivalent. The possible radical scavenging antioxidant activity of the methanol extract was investigated in vitro methodology using 2, 2-diphenyl-1-picryl-hydrazyl (DPPH) and total reducing power was compared with that of ascorbic acid as a standard compound. The obtained results were substantial. So, study was extended for gummy mass of crude methanol extract (B) and hexane fraction of gummy mass of crude methanol extract (C).